Kegiatan Ekstrakurikuler dan Keterlibatan Mahasiswa: Dampak terhadap Pembangunan Karakter dan Kemampuan Kepemimpinan - Patra, I Ketut; Rachman, Muh. Ade; Rismawati, Rismawati (Universitas PGRI Madiun, 2024)
This study aims to determine the importance of understanding the impact of extracurricular activities on the development of student character and leadership abilities. This research is qualitative research with descriptive methods, because this research aims to get an in-depth picture. The data collection techniques used are observation, interviews, and documentation. The results of this study show that extracurricular activities in fostering student character have a significant positive impact on student character building, especially in the development of social skills, ethics, and personal values that support positive character. Existing research and theory support this positive relationship, and extracurricular activities give students the opportunity to internalize that character. In addition, extracurricular activities can also play an important role in the development of student leadership abilities, by providing experience in organizing, motivating, and managing conflicts. However, it is important to realize the importance of supporting and encouraging active participation of students in extracurricular activities as an integral part of higher education. Educational institutions need to provide financial and non-material support, as well as competent human resources in managing extracurricular activities.